Pengembangan Web Service Sistem Informasi Boarding School - Bachriwindi, Aniqoh; Zaman, M. Robih Thuluz; Firdaus, Muhammad Naufal; Yaqin, Muhammad Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
The boarding school information system is a system that provides information to support the operational, management, and decision making functions of an organization. Information sources within the information system that support day-to-day management operations such as transaction processing, status clarification, and so on. Boarding school information systems generally consist of a variety of systems, including welfare systems, management, premises, procedures and policies, and staffing. With a variety of systems in a boarding school information system, it is necessary to integrate between systems that aim to avoid data duplication in each system and increase system flexibility which can be achieved by utilizing web service technology. The purpose of this study is to design a web service on boarding school information systems that conform to 52 boarding school minimum standards set by the Welsh Assembly Government. The results of the development of an information system web service design is to map class diagrams that will be made on the web service design.